Evaluating Prior Learning Assessment Programs: A Suggested Framework - Travers, Nan L.; Evans, Marnie T. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Over the past two decades, American institutions have been expected to include systematic program reviews to meet accrediting standards, either by independent or governmental review agencies. Program evaluation is critical for several reasons: it provides systematic ways to assess what needs improvement or what needs changing and it provides ways to validate practices, whether to internal or external audiences (Mishra, 2007). Most program evaluative models are focused on academic programs, which don’t fit the uniqueness of prior learning assessment programs. This paper proposes an evaluative framework for prior learning assessment programs, which takes into account the type of work within prior learning assessment programs and uses program portfolios, similar to how students are asked to document their work.